Performa dan Bobot Organ Pencernaan Ayam Broiler yang Diberi Pakan Limbah Udang Hasil Fermentasi Bacillus sp. - I H Djunaidi; T Yuwanta; Supadmo Supadmo; M Nurcahyanto (Faculty of Animal Science, Bogor Agricultural University, 2009)
An experiment examined the effect of the inclusion of different levels of shrimp waste meal (LUFb) fermented with Bacillus sp. in diets on growth performance and digestive organ weight of broilers. A total of 75 d-old broiler chicks were randomized in five treatments with 3 replicate pens of 5 birds each. Treatments consisted of 0 (control), and inclusion of LUFb of 5%, 7.5%, 10%, and 12,5% in the diets. Birds were offered with feed and water ad-libitum. Feed and birds were weighed weekly up to 35 day to calculate determine body weight gain, feed intake and feed conversion. At the end of experimental period, the birds were sacrificed and dress up to calculate carcass percentage and digestive organ weight. There was a significant negative linear response in body weight, feed consumption and feed conversion with increasing of LUF more than 5% in the diets, but carcass percentage was almost the same for all treatments. There was no significant response in digestive organ weight with increasing levels of LUF. The present result indicated that LUFb is potential feed ingredient to substitute part of dietary protein requirement of broiler but should be limited upto 5% to maintain growth performance, and digestive organ weight. Key words: shrimp waste meal, broiler, digestive organ